2009
DOI: 10.1108/17506120910989651
|View full text |Cite
|
Sign up to set email alerts
|

Wealth effects of the pharmaceutical industry‐physician interaction compliance guidelines on large pharmaceutical companies

Abstract: Purpose -The purpose of this paper is to investigate the wealth effects of the issuance of guidelines by the Office of Inspector General (OIG) to encourage pharmaceutical manufacturers to use internal controls or self-regulation "to efficiently monitor adherence to applicable statutes, regulations, and program requirements" in their marketing to the physicians. Design/methodology/approach -The authors employ a standard event-study methodology to examine the impact on shareholders of 12 large pharmaceutical fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As mentioned earlier, recent research documented the significant wealth effects of OIG’s guidance not only on Big PHARMA but also on biotechnology firms. 7,8 For the purpose of this paper, we are investigating the OIG’s impact on the share prices of generic firms. This intra-industry impact or contagion phenomenon is of interests to policy makers and regulators as further policy changes may be contemplated.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned earlier, recent research documented the significant wealth effects of OIG’s guidance not only on Big PHARMA but also on biotechnology firms. 7,8 For the purpose of this paper, we are investigating the OIG’s impact on the share prices of generic firms. This intra-industry impact or contagion phenomenon is of interests to policy makers and regulators as further policy changes may be contemplated.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Based on the above, we can propose that the inter-industry contagion can be extended to generic industry since the prior evidence has shown that a certain regulatory event (in this case, OIG’s Guidance) has negatively impacted both the Big Pharma 8 and the biotechnology industry. 7…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The diverse forms of economic consumption have always interested marketing professionals and academics alike. The use of prescription drugs has been studied by several authors, both in terms of the growth of the pharmaceutical industry (Kim and King, 2009; Fogel and Novick, 2009; Delorme et al , 2009; Limbu and Torres, 2009) and the specificity of consumption in this industry (Diehl et al , 2008; Miao‐Sheng and Yu‐Ti, 2008; Kess et al , 2008; Jambulingam et al , 2009).…”
Section: Introductionmentioning
confidence: 99%